Impact of drug therapy on brachioradial pruritus - Patrick Alexander Wachholz; Paula Yoshiko Masuda; Ana Cecília Versiani Duarte Pinto; Antônio Carlos Ceribelli Martelli (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Few studies have described therapeutic options in brachioradial pruritus. We describe a cross-sectional study of brachioradial pruritus patients treated in an outpatient unit. We reviewed medical records and interviewed brachioradial pruritus patients without indication for decompressive surgery, in order to access the perceptions of intensity of pruritus prior to treatment and response to therapy. We found that antidepressants and anticonvulsants were the most frequently prescribed drugs. Best reductions in pruritus were associated with its highest intensities prior to treatment, and with longer periods of therapy.